Consent Legacies, Representations, and Frameworks for the Future - Franklin, Sophie; Piercy, Hannah; Thampuran, Arya; White, Rebecca (Taylor & Francis, 2024)
While consent tends to be most commonly foregrounded in discourse surrounding sex and sexuality, Consent: Legacies, Representation, and Frameworks for the Future seeks to unpack the term in all its wide-ranging social, ideological, and cultural entanglements. With its diverse conceptual scope, commitment to cross-disciplinary and cross-cultural research, this edited collection works to broaden the conception of 'consent' as an evolving entity in both theory and practice by foreground disciplinary diversity. The chapters are grouped into five sections: 'Culture and Resistance'; 'Consent on Screen'; 'Coercion and Violence'; 'Practice and Pedagogies'; and 'Futures of Consent', each presenting plural articulations of consent as it circulates across contemporary life, from media and cultural production to technology and pedagogy. Consent: Legacies, Representation, and Frameworks for the Future is of value to undergraduate and graduate students studying gender studies, sociology, media studies and law.